Young children's food in Liverpool day-care settings: a qualitative study of pre-school nutrition policy and practice - Lloyd-Williams, Ffion; Bristow, Katie; Capewell, Simon; Mwatsama, Modi (Public health nutrition, 2011)
Objective To explore nutrition and food provision in pre-school nurseries in order to develop interventions to promote healthy eating in early years settings, especially across deprived communities. Design An ethnographic approach was used combining participant observation with semi-structured interviews. Research participants were selected purposively using convenience sampling. Setting Community pre-school nurseries. Subjects Nursery managers (n 9), cooks (n 6), staff (n 12), parents (n 12) and children at six nurseries (four private and two attached to children's centres) in Liverpool, UK. Results Private nurseries had minimal access to information and guidelines. Most nurseries did not have a specific healthy eating policy but used menu planning to maintain a focus on healthy eating. No staff had training in healthy eating for children under the age of 5 years. However, enthusiasm and interest were widespread. The level and depth of communication between the nursery and parents was important. Meal times can be an important means of developing social skills and achieving Early Years Foundation Stage competencies. Conclusions Nurseries are genuinely interested in providing appropriate healthy food for under-5s but require support. This includes: improved mechanisms for effective communication between all government levels as well as with nurseries; and funded training for cooks and managers in menu planning, cost-effective food sourcing and food preparation. Interventions to support healthy eating habits in young children developed at the area level need to be counterbalanced by continued appropriate national-level public health initiatives to address socio-economic differences.